Dislocation characterization in c-plane GaN epitaxial layers on 6 inch Si wafer with a fast second-harmonic generation intensity mapping technique. (9th April 2023) - Chiang, Shou-En; Chang, Wen-Hsin; Chen, Yu-Ting; Li, Wen-Chung; Yuan, Chi-Tsu; Shen, Ji-Lin; Chang, Sheng Hsiung
Abstract: Second harmonic generation (SHG) intensity, Raman scattering stress, photoluminescence and reflected interference pattern are used to determine the distributions of threading dislocations (TDs) and horizontal dislocations (HDs) in the c -plane GaN epitaxial layers on 6 inch Si wafer which is a structure of high electron mobility transistor (HEMT). The Raman scattering spectra show that the TD and HD result in the tensile stress and compressive stress in the GaN epitaxial layers, respectively. Besides, the SHG intensity is confirmed that to be proportional to the stress value of GaN epitaxial layers, which explains the spatial distribution of SHG intensity for the first time. It is noted that the dislocation-mediated SHG intensity mapping image of the GaN epitaxial layers on 6 inch Si wafer can be obtained within 2 h, which can be used in the optimization of high-performance GaN based HEMTs.